Acute effects of foam rolling on blood flow measured by ultrasonography in soccer players - Alonso-Calvete, A.; Padrón-Cabo, A.; Lorenzo-Martínez, M.; Rey, E. (The Journal of Strength and Conditioning Research, 2021)
In recent years, foam rolling (FR) has become a popular device for recovery to increase range of motion and decrease pain after sport practice and competition. However, there is little evidence about the underlying physiological effects of FR, specifically in blood flow parameters. Thus, the aim of this study was to analyze acute effects of FR on blood flow parameters (maximal velocity and maximal volume) measured by Doppler ultrasonography in soccer players. Twelve soccer players were assessed in 3 different situations: pre-FR intervention, immediately after FR intervention, and 30 minutes after FR intervention. The femoral artery was measured in the dominant leg with subjects in horizontal lying position. Before the intervention, subjects completed one familiarization session with FR. The FR intervention consisted of 2 sets, each with 45 seconds of FR and 15 seconds of rest between sets with a high-density foam roller in quadriceps, hamstrings, and iliotibial band. Results showed a significant increase in both maximal velocity (p < 0.001; effect size [ES] = 0.81) and maximal volume (p = 0.001; ES = 1.73) after intervention in comparison with pretest, but after 30 minutes, there were no significant differences. Therefore, this increase of the blood flow could promote important advantages for postexercise recovery, suggesting an acute effect that may contribute to the understanding of local physiological mechanism of FR.